Pengaruh Bimbingan Kelompok Berbantuan Media Vision Board terhadap Perencanaan Karier Siswa SMP - Wulanayupuspa Nugraheni; Siti Rahmi (Universitas Palangka Raya, 2026)
This study aimed to examine differences in students’ career planning before and after participating in group guidance assisted by vision board media at SMP Negeri 14 Tarakan. This study employed a quantitative approach using a pre-experimental design with a one-group pretest-posttest design. The population consisted of 128 eighth-grade students at SMP Negeri 14 Tarakan, while the sample consisted of eight students selected through a random sampling technique assisted by the Wheel of Names application, in which two students were randomly selected from each class. The research instrument was a career planning questionnaire developed using a Likert scale based on four career planning indicators proposed by Hamzah, namely awareness of career insight and preparation, understanding alternative career considerations, having future career planning, and developing career readiness. The group guidance service assisted by vision board media was conducted in eight sessions. Data were analyzed using descriptive and inferential statistics through the paired sample t-test with the assistance of IBM SPSS Statistics 21. The results showed that the mean career planning score increased from 137.00 in the pretest to 158.38 in the posttest, with the highest improvement found in the career readiness indicator. The paired sample t-test yielded a significance value of 0.001 (p < 0.05), indicating a significant difference between students’ career planning scores before and after participating in the service. These findings suggest that group guidance assisted by vision board media has the potential to improve students’ career planning. However, the findings should be interpreted with caution due to the limitation of the one-group pretest-posttest design without a control group.